The role of adversity quotient on job crafting during the pandemic: Peran adversity quotient terhadap job crafting di masa pandemi - Myra Yuliza; Ferry Novliadi (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
This study examines the role of adversity quotient on job crafting. This survey involving employees of a banking company in the city of Medan shows that a high adversity quotient is positively related to job crafting. Penelitian ini menelaah peran adversity quotient terhadap job crafting. Survey yang melibatkan karyawan suatu perusahaan perbankan di kota Medan ini menunjukkan bahwa adversity quotient yang tinggi berelasi positif dengan job crafting.